Administration of Eucalyptus to Inhibit the Skin Aging Process of Rats (Rattus Norvegicus) Wistar Strains Exposed to Ultraviolet-B Light - Asira Mahrahmi; Tan Suyono; Ali Napiah Nasution (International Journal of Health and Pharmaceutical (IJHP), 2024)
Ageing weakens the skin's protective layer, causing pigmentation, inflammation, and cancer. Environmental hazards like pollution and UV radiation harm the skin. Antioxidants, like Eucalyptus globulus, protect against free radicals, making them valuable in medicinal use. The study aimed to investigate the efficacy of Eucalyptus administration in inhibiting skin ageing in rats exposed to ultraviolet-B light. A true experiment was conducted to examine the effectiveness of Eucalyptus in reducing skin ageing in Wistar rats exposed to ultraviolet-B radiation. The study used the "3R Principle" and SPSS to analyse the relationship between collagen quantity, Eucalyptus, and UVB radiation. The study found normal distribution for the control and treatment groups, with a significance of 0.200 and 0.091, respectively. The Levene test showed homogeneity and a T-test result 0.000, indicating a significant difference. The control group had a moderate collagen density, while the treatment group with Eucalyptus extract had a tighter collagen density. The study concludes that the Eucalyptus tree extracts, including tannins, saponins, and flavonoids, have been found to have anti-ageing and collagen-increasing effects in mice exposed to UVB light. The treatment group showed significantly increased collagen density, indicating potential anti-ageing properties in the treatment group.